Factors contributing to serious adverse events in nursing homes. Issue 1 (4th December 2017) - Andersson, Åsa; Frank, Catharina; Willman, Ania ML; Sandman, Per‐Olof; Hansebo, Görel
Abstract : Aims and objectives: To identify the most common serious adverse events that occurred in nursing homes and their most frequent contributing factors to the improvement of safe nursing care. Background: There is a need to improve safe nursing care in nursing homes. Residents are often frail and vulnerable with extensive needs for nursing care. A relatively minor adverse event in nursing care can cause serious injury that could have been preventable. Design: This was a retrospective study, with a total sample of data regarding adverse events ( n = 173) in nursing homes, concerning nursing care reported by healthcare providers in Sweden to the Health and Social Care Inspectorate. The reports were analysed with content analysis, and the frequencies of the adverse events, and their contributing factors, were described with descriptive statistics. Results: Medication errors, falls, delayed or inappropriate intervention and missed nursing care contributed to the vast majority (89%) of the serious adverse events. A total of 693 possible contributing factors were identified. The most common contributing factors were (i) lack of competence, (ii) incomplete or lack of documentation, (iii) teamwork failure and (iv) inadequate communication. Conclusions: The contributing factors frequently interacted yet they varied between different groups of serious adverse events. The resident's safety depends on the availability of staff's competence as well as adequate documentation about the resident's condition. Lack of competence was underestimated by healthcare providers. Relevance to clinical practice: Registered nurses and assistant nurses need to have awareness of contributing factors to adverse events in nursing care. A holistic approach to improve patient safety in nursing homes requires competence of the staff, safe environments as well as resident's and relative's participation.